On the Frame Properties of Degenerate System of Sines - Bilal Bilalov; Fatima Guliyeva (Journal of Function Spaces and Applications)
Systems of sines with degenerate coefficients are considered in this paper. Frame properties of these systems in Lebesgue spaces are studied.